AMÉLIORATION DES PERFORMANCES DE L’UTG DE GUELLALA PAR L’AJOUT D’UN NOUVEAU SECHEUR : ÉTUDE TECHNICO-ÉCONOMIQUE - Aimen DJELLOULI (My University, 2026)
This thesis evaluates the feasibility of installing a fourth molecular sieve dryer at the Guellala Gas Treatment Unit (UTG/GLA) in Haoud Berkaoui. The current three-dryer system suffers from adsorbent degradation, limited regeneration flexibility, and frequent maintenance shutdowns, leading to increased water content and reduced reliability. A technical analysis and sizing study for a fourth dryer (V-403 D) were conducted using GPSA methodologies and real operating data. The proposed four-dryer configuration (2 operating + 1 regenerating + 1 standby) enhances operational flexibility, ensures service continuity, and optimizes regeneration cycles. An economic assessment based on actual production losses confirms the investment is highly profitable with a short payback period and positive Net Present Value (NPV). Installing a fourth dryer represents a reliable, sustainable solution for improving dehydration performance and securing gas lift supply. ------------------------------------------------------------------ تتناول هذه المذكرة دراسة جدوى تركيب مجفف رابع بالغربال الجزيئي في وحدة معالجة الغاز UTG/GLA بمنطقة حوض بركاوي. يعاني النظام الحالي المكون من ثلاث مجففات من تدهور أداء الغربال والتوقفات المتكررة للصيانة وارتفاع نسبة الماء في الغاز المعالج، مما يؤدي لتشكل الهيدرات وخسائر إنتاجية. أظهرت الدراسة التقنية وعمليات التصميم أن التشغيل بنظام (2+1+1) يعزز المرونة التشغيلية واستمرارية الخدمة. كما أثبتت الدراسة الاقتصادية المعتمدة على خسائر الإنتاج الحقيقية أن المشروع مربح للغاية بفترة استرداد قصيرة وقيمة حالية صافية إيجابية. يُعدّ تركيب المجفف الرابع حلاً تقنيًا واقتصاديًا مناسبًا لتحسين موثوقية نظام نزع الماء وضمان استقرار تشغيل الوحدة ------------------------------------------------------------------ Ce mémoire évalue la faisabilité de l'installation d'un quatrième sécheur à tamis moléculaires à l'unité de traitement de gaz UTG/GLA de Guellala. Le système actuel à trois sécheurs présente des limites opérationnelles : dégradation progressive des tamis, arrêts fréquents pour maintenance et teneur en eau élevée du gaz traité, favorisant la formation d'hydrates et de perturbations. L'étude technique et les calculs de dimensionnement proposent une nouvelle configuration (2+1+1), offrant une meilleure flexibilité et continuité de service. L'évaluation économique, basée sur les pertes de production réelles, confirme que l'investissement est très rentable avec un délai de récupération court et une valeur actuelle nette positive. L'installation d'un quatrième sécheur constitue ainsi une solution fiable et durable pour améliorer la performance de déshydratation et sécuriser l'approvisionnement en gaz lift.
Keywords: : Dryer; Molecular sieves; Dehydration; Adsorption; UTG/GLA gas treatment unit.; مجفف؛ مناخل جزيئية؛ تجفيف؛ امتزاز؛ وحدة معالجة الغاز UTG/GLA: Sécheur; Tamis moléculaires; Déshydratation; Unité de traitement de gaz UTG/GLA.